Divine Justice/Divine Command - Novak, David (Studies in Christian ethics, 2010)
In the Jewish tradition there are those who simply identify divine justice with the specific divine commands, which is a theological version of legal positivism. This paper argues for another view in the Jewish tradition, viz., divine justice or divine wisdom is the rationale of the specific divine commands, thus making them more than arbitrary decrees. As the rationale of the specific divine commands, divine justice functions as a criterion of judgment that prevents irrational interpretations and unjust applications of the specific divine commands. This approach is a theological version of natural law.